2008
DOI: 10.1177/019874290803300404
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Effects of Check-in/Check-out with Function-Based Support

Abstract: Targeted interventions (also called Tier 2 interventions or secondary interventions) are implemented within a comprehensive three-tiered system of support consisting of universal interventions (for all students), targeted interventions (for students exhibiting mild behavioral difficulties), and intensive interventions (for students requiring individualized support). Check-in/check-out is a targeted intervention designed to reduce incidences of disruptive behavior and increase prosocial behavior. Although check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 21 publications
2
107
0
2
Order By: Relevance
“…Students' progress was graphed in two studies (Lane et al, 2012;Simonsen et al, 2011). In terms of outcomes, a functional relation between CICO (or variations) and dependent variables was reported by authors in 4 of 15 single-subject studies, indicating increases in daily report card ratings (Campbell & Anderson, 2008;Dart et al, 2014;Lane et al, 2012) and academic engagement (Campbell, Rodriguez, Anderson, & Barnes, 2013), and decreases in problem behaviors such as disruption (Campbell & Anderson, 2008;Campbell et al, 2013). In one singlesubject study, a functional relation was discussed by authors who indicated one could not be established due to the limitation of the design (i.e., AB design; Swoszowski, Jolivette, & Fredrick, 2013).…”
Section: Cico Variationsmentioning
confidence: 99%
“…Students' progress was graphed in two studies (Lane et al, 2012;Simonsen et al, 2011). In terms of outcomes, a functional relation between CICO (or variations) and dependent variables was reported by authors in 4 of 15 single-subject studies, indicating increases in daily report card ratings (Campbell & Anderson, 2008;Dart et al, 2014;Lane et al, 2012) and academic engagement (Campbell, Rodriguez, Anderson, & Barnes, 2013), and decreases in problem behaviors such as disruption (Campbell & Anderson, 2008;Campbell et al, 2013). In one singlesubject study, a functional relation was discussed by authors who indicated one could not be established due to the limitation of the design (i.e., AB design; Swoszowski, Jolivette, & Fredrick, 2013).…”
Section: Cico Variationsmentioning
confidence: 99%
“…The research support for CICO is strong and comes largely from single-case research documenting functional relations between tbe implementation of CICO and a reduction in problem bebavior (Campbell & Anderson, 2008;Crone et al, 2010;Hawken, 2006;Hawken & Horner, 2003;Hawken, MacLeod, & Rawlings, 2007;March & Horner, 2002;McCurdy, Kunsch, & Reibstein, 2007;Todd, Kaufman, Meyer, & Horner, 2008) …”
Section: Check-in/check-outmentioning
confidence: 99%
“…For students who fail to respond to Tier 2 supports, implementing additional Tier 3, function-based interventions is effective in decreasing problem behavior (Campbell & Anderson, 2008;Carter & Horner, 2007;Carter & Horner, 2009;Fairbanks et al, 2007;Lane et al, 2007;Lane, Kalberg, & Shepcard, 2009;March & Horner, 2002;Nahgahgwon, Umbreit, Liaupsin, & Turton, 2010;Trussell, Lewis, & Stichter, 2008). Function-based interventions involve conducting a functional behavioral assessment to determine why the student is engaging in problem behavior and using the information to develop a behavior support plan (O'Neill et al, 2014;Umbreit, Ferro, Liaupsin, & Lane, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A small number of studies have evaluated the effectiveness of adding function-based tier 3 supports for students non-responsive to CICO (Campbell & Anderson, 2008;Fairbanks et al, 2007;March & Horner, 2002). March and Horner (2002) found that function-based additions to CICO for three sixth and seventh grade students helped reduce their observed rates of problem behavior and improved their academic engagement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation